Comprehensive analysis of molecular features, prognostic values, and immune landscape association of m6A-regulated immune-related lncRNAs in smoking-associated lung squamous cell carcinoma - Zhang, Meng; Zhang, Jian; Liu, Yang (Frontiers in Genetics, 2022)
Lung squamous cell carcinoma (LUSC) is the second most common histopathological subtype of lung cancer, and smoking is the leading cause of this type of cancer. However, the critical factors that directly affect the survival rate and sensitivity to immunotherapy of smoking LUSC patients are still unknown. Previous studies have highlighted the role of N6-methyladenosine (m6A) RNA modification, the most common epigenetic modification in eukaryotic species, together with immune-related long non-coding RNAs (lncRNAs) in promoting the development and progression of tumors. Thus, elucidating m6A-modified immune lncRNAs in LUSC patients with smoking history is vital. In this study, we described the expression and mutation features of the 24 m6A-related regulators in the smoking-associated LUSC cohort from The Cancer Genome Atlas (TCGA) database. Then, two distinct subtypes based on the expression levels of the prognostic m6A-regulated immune lncRNAs were defined, and differentially expressed genes (DEGs) between the subtypes were identified. The distributions of clinical characteristics and the tumor microenvironment (TME) between clusters were analyzed. Finally, we established a lncRNA-associated risk model and exhaustively clarified the clinical features, prognosis, immune landscape, and drug sensitivity on the basis of this scoring system. Our findings give insight into potential mechanisms of LUSC tumorigenesis and development and provide new ideas in offering LUSC patients with individual and effective immunotherapies.